Expression of EpCAM Increases in the Hepatitis B Related and the Treatment-Resistant Hepatocellular Carcinoma. (17th February 2014) - Kimura, Osamu; Kondo, Yasuteru; Kogure, Takayuki; Kakazu, Eiji; Ninomiya, Masashi; Iwata, Tomoaki; Morosawa, Tatsuki; Shimosegawa, Tooru
Abstract : Increasing evidence supports the important role of cancer stem cells (CSCs). Many reports suggest that epithelial cell adhesion molecule (EpCAM) is a useful marker for cancer stem cells in hepatocellular carcinoma (HCC). To elucidate the mechanisms of cancer stem cells, the development of specific molecular targeted drugs has become very important. In the present study, we examined the EpCAM expression pattern and its characteristic expression in resected HCC. We studied the drug resistance of EpCAM expression cells. EpCAM expression was detected significantly more frequently with hepatitis B virus (HBV) than with other etiologies. In HCC resection patients who had received prior treatment (transcatheter arterial embolization or hepatic arterial infusion chemotherapy), EpCAM was strongly expressed. In particular, very strong expression was observed after hepatic arterial infusion chemotherapy. The PLC/PRF/5 human HCC cell line expressed bimodal EpCAM, and EpCAM-positive cells had CSC cell potency. The EpCAM expression in EpCAM-positive cells increased significantly by treatment with cisplatin. EpCAM-positive cells showed better viability than EpCAM-negative cells when treated with ciplatin. Collectively, our results suggest that cancer stem cells are highly expressed in hepatitis B and have potential anticancer drug resistance.